Systematic Studies of the Genus Asparagus Tourn. Ex Linn. (Liliaceae) In Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
The genus Asparagus Tourn. ex Linn. represented by five species in Bangladesh, viz., Asparagus adscendens Roxb., A. densiflorus (Kunth) J.P. Jessop, A. officinalis L., A. racemosus Willd. and A. setaceus (Kunth) J.P. Jessop is revised. Each species is described with updated nomenclature, important synonyms, phenology, specimens examined, chromosome number, habitat, distribution, economic value and mode of propagation. A dichotomous bracketed key to the species and illustrations along with photographs of four species are provided.Bangladesh J. Plant Taxon. 29(1): 97-107, 2022 (June)